Actualizing Maqam Qanaah in Responding to the Consumptive Lifestyle of the Younger Generation - Nasution, Dwi Rizki Nabila; Faishal, Muhammad (Madania: Jurnal Ilmu-Ilmu Keislaman, 2025)
The consumptive lifestyle of the younger generation in Sigara-gara Village, Patumbak Sub-district is influenced by the rapid development of technology and materialistic tendencies. This can be seen by the purchase of goods that are not basic needs in order to build self-image and fulfill social pressure. This research aims to find out how the younger generation perceives and practices maqam qanaah in overcoming their consumerism. The method used is a qualitative approach that focuses on case studies. Data was collected through in-depth interviews with six young people aged 20-27 years old. After the data was collected, it was analyzed using the Miles and Hubarman model. The findings of this study show that maqam qanaah can be actualized through three ways, first by providing religious education through religious studies and examples from parents. Second, by changing the mindset to be more grateful and being in an environment that supports the value of qanaah. Third, wise financial management by keeping a record of expenses every month to avoid impulsive buying and saving for the future. These findings are contextual and cannot be generalized widely due to the small number of respondents and the limited scope of the region. Therefore, other research is needed with a broader approach and coverage area. This research makes a significant contribution to the development of contextual Sufism, by connecting maqam qanaah with the challenges of modern life.